Development of a Tulungagung Batik Booklet as an Ethnoscience-Based Chemistry Learning Resource - Silfianah, Ifah; Tutik Sri Wahyuni (Orbital: Jurnal Pendidikan Kimia, 2025)
Tulungagung Batik is a culture that needs to be introduced to chemistry students. One of the efforts is to provide a chemistry booklet with the theme Batik Tulungagung. Students have never used booklets based on ethnoscience. This research aims to develop a chemistry booklet based on Tulungagung Batik ethnoscience, describing the feasibility and student responses to the booklet developed. The research method used is research and development using a 4D model. This research involved 67 students who filled out questionnaires, three lecturers as validators, and five students who were interviewed. The instruments used are a needs questionnaire, interview sheet, validation sheet, and response sheet. Data in the form of suggestions and interview results were processed qualitatively, while data from validation and questionnaires were processed descriptively qualitatively. The research results showed that the suitability of the Tulungagung Batik ethnoscience booklet in terms of content was 95.24%, a presentation was 94.44%, language was 90.37%, and graphics was 90.67%. The student response to the Tulungagung Batik ethnoscience booklet was 85.86%. Thus, the booklet developed is very good for use as an independent learning resource in studying chemistry.